2015
DOI: 10.1016/j.jcmg.2015.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial on Radiation Dose Estimates of CT Angiography Applying Iterative Image Reconstruction

Abstract: Coronary CTA image quality is maintained with the combined use of a 30% reduced tube current and IR algorithms when compared with conventional FBP image reconstruction techniques and standard tube current. (Prospective Randomized Trial On RadiaTion Dose Estimates Of CT AngIOgraphy In PatieNts: NCT01453712).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…FIRST showed 28% dose reduction compared to AIDR-3D (23). The PROTECTION V study, a large, prospective, multi-center, multi-vendor, randomized-control trial of 400 patients found that image quality of coronary CTA performed at 30% reduced tube current and reconstructed with multiple IR algorithms (ASIR, SAFIRE, iDose 4 , AIDR-3D) matched standard tube current coronary CTA reconstructed with FBP (24). Improved image quality for low-dose (submillisievert) coronary CTA was observed with a modelbased algorithm, IMR, compared to standard FBP (25).…”
Section: Decreased Radiation Dosementioning
confidence: 99%
“…FIRST showed 28% dose reduction compared to AIDR-3D (23). The PROTECTION V study, a large, prospective, multi-center, multi-vendor, randomized-control trial of 400 patients found that image quality of coronary CTA performed at 30% reduced tube current and reconstructed with multiple IR algorithms (ASIR, SAFIRE, iDose 4 , AIDR-3D) matched standard tube current coronary CTA reconstructed with FBP (24). Improved image quality for low-dose (submillisievert) coronary CTA was observed with a modelbased algorithm, IMR, compared to standard FBP (25).…”
Section: Decreased Radiation Dosementioning
confidence: 99%
“…This image reconstruction algorithm allows a significant improvement in image quality, thus enabling the achievement of similar image quality at reduced radiation doses. In this way a stress-rest or rest-stress myocardial CTP can be done with less than 9 mSv, achieving similar radiation doses than a SPECT scan (58,59).…”
Section: Iterative Reconstruction (Ir)mentioning
confidence: 99%
“…56,57 Recent technical developments including new detector material and integrated circuit detector, low kV (70-80 KV) protocol, new iterative reconstruction and motioncorrection algorithms represent yet another milestone for substantial dose reduction, while the CT image quality may be further improved. [56][57][58][59] Diagnostic performance and prognostic value of cardiac CT Cardiac CT has emerged as the mainstay diagnostic tool for non-invasive anatomical assessment of coronary atherosclerosis.…”
Section: Cardiac Ctmentioning
confidence: 99%